Matrici romano-milanesi nella poetica architettonica di Luigi Moretti. 1948-1960 - Ricciuti, Valentina (Premio Ricerca «Città di Firenze», 2012)
Ricciuti starts from an analysis of some of the most significant projects from the post-war period to identify, for each of the cultural spheres geographically defined by the cities of Rome and Milan, a series of recurring characteristics and motifs that can be traced back to the maestro's desire to maintain a coherent language, albeit in a dual thematic register. Within the assertion that there exists a specificity to Moretti's work, and a close relationship with the different contexts, the author investigates this duality while seeking an alliance with literature and art criticism. This she does by recalling terms belonging to the language of artistic exegesis, but also by citing some authoritative contributions to the history of poetry and of European literature from the twentieth century and much more besides.